Evaluation of Career Guidance and Counseling Program through Accountability Model Bridge - Utami, Ferisa Prasetyaning (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The Accountability Model Bridge is a solution for school counsellors in evaluating counselling programs, especially in the career field, based on a framework that contains the stages of evaluating guidance and counselling programs. This Bridge Model evaluation is interrelated between (1) the counselling program evaluation cycle and (2) the counselling context evaluation cycle. Career guidance and counselling program need to be evaluated for its achievement to see how effective it is and how it impacts students. The Accountability Model Bridge is a framework that can assist counsellors in facilitating the implementation of program evaluations involving school stakeholders. The existence of this Bridge Model can provide an effect and understanding for school administrators about the benefits of the career counselling program that is followed by students which later can be used as the basis for continuous program improvement. The counsellor can carry out guidance and counselling programs effectively. Keywords: Accountability, Career Guidance and Counseling, Bridge Model